Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Loyalitas Nasabah PT. Bank Nagari Unit Syariah Cabang Tapan Dengan Kepuasan Sebagai Variabel Intervening - Elex Sarmigi; Muhammad Alfian; Tia Septiani; Rizky Aldiansyah; Rudi Wahyudi (Tasharruf : Journal of Islamic Economics and Business, 2023)
This study aims to determine how strong the influence of service quality and trust on customer loyalty with satisfaction as an intervening variable at Bank Nagari Syariah Unit Tapan Branch. Agency theory is used to describe the quality of Service Quality and Trust in Customer Loyalty with Satisfaction as an intervening variable. This research is a type of quantitative research. Quantitative analysis in this study is needed to provide an overview of the results of the study, then in order to strengthen the existence of a use of interest in being a customer between variables, it requires proof of analysis carried out on the answers to the results of the questionnaire distributed to respondents. This study aims to find an explanation of the influence of the quality of service quality and trust. The results show that service quality has a positive and significant effect on customer satisfaction. The higher the quality of the services provided, the higher the customer satisfaction that can be achieved. Trust has a positive and significant effect on customer satisfaction. The higher the quality of the performance of a banking trust, the higher the customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty. The creation of high satisfaction allows customers to remain loyal to the banking trust used.